Influence of light curing units on failure of directcomposite restorations - Jadhav, Sameer (Medknow Publications, 2011)
Light polymerizable tooth colored restorative materials are most widely preferred for advantages such as esthetics, improved physical properties and operator's control over the working time. Since the introduction of these light polymerizable restorative materials, there has been a concern about the depth of appropriate cure throughout the restoration. Photopolymerization of the composite is of fundamental importance because adequate polymerization is a crucial factor for optimization of the physical and mechanical properties and clinical results of the composite material. Inadequate polymerization results in greater deterioration at the margins of the restoration, decreased bond strength between the tooth and the restoration, greater cytotoxicity, and reduced hardness. Therefore, the dentist must use a light curing unit that delivers adequate and sufficient energy to optimize composite polymerization. Varying light intensity affects the degree of conversion of monomer to polymer and depth of cure.